Playgrounds in perspective; an exploration of the Swedish schoolyard development - Booshi, Fatima (My University, 2024)
The schoolyard is a natural part of our school system, present in all Swedish schools. Most individuals who have attended school have some kind of memory associated with it and the time they spent there. The significance of play for children’s well-being and development is widely acknowledged, with evidence suggesting its positive impact on mental and physical health. Play theory asserts that play is fundamental to human behavior. It highlights play as crucial for children’s language development and understanding of the world (Tanis, 2012). Among various settings, the schoolyard stands out as an ideal space to encourage children’s play and activity during recess (Delidou, Matsouka & Nikolaidis, 2015. p.2). Seven out of ten children are moving less than recommended in Sweden according to the Swedish food agency (livsmedelsverket). The study shows a difference between genders, ages, and parents’ educational level. It also shows that children are more physically active during school hours compared to other times of the day (Livsmedelsverket 2016). Considering the substantial amount of time children spend at school, an outdoor school environment can effectively promote and support students’ engagement in physical activities as much as it can inhibit it, if not well equipped. Laws and regulations, as well as municipal guidelines exist to aid in the planning of outdoor spaces within schools, the main focus is around the concerning trend of shrinking schoolyards due to urbanization and policy decisions. Despite this being an important point to consider, today we can observe schools with adequately sized schoolyards that lack in other aspects. The debate surrounding regulations for schoolyard spaces has sparked political discussions, with architects and urban planners emphasizing the need for qualitative as well as quantitative considerations. This thesis delves into the historical evolution of schoolyards to understand its developments and context through time. It also examines its impact on children’s play, cognitive and social development. Furthermore, it investigates how conceptual design elements can be applied in existing schoolyards in Gothenburg amidst evolving societal and environmental dynamics.